2007
DOI: 10.1557/jmr.2007.0409
|View full text |Cite
|
Sign up to set email alerts
|

Layered stacking characteristics of ternary zirconium aluminum carbides

Abstract: Layered stacking characteristics of ternary Zr-Al-C carbides were investigated using scanning transmission electron microscopy (STEM). Three previously unknown compounds, i.e., Zr 4 Al 3 C 6 , Zr 5 Al 6 C 9 , and Zr 7 Al 6 C 11 were identified. The present study extends the structural information of ternary Zr-Al-C ceramics. The influence of the thickness of the NaCl-type Zr-C slab on the elastic properties of ternary Zr-Al-C ceramics is discussed based on first-principles calculations. In addition, direct ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The C–C distances at the layer boundaries are nearly equal to each other (0.3328 nm for m =1 and 0.3325 nm for m =2) and also comparable to those of the ZrC and Al 4 C 3 crystals, in accord with the principle of the formation of layered carbides in the Zr–Al–C system 2 . The principle could also be applicable to the recently reported layered carbides Zr 4 Al 3 C 6 , Zr 5 Al 6 C 9 , and Zr 7 Al 6 C 11 14 . However, these materials were only recognized under TEM; hence, a precise structural characterization would be needed for further discussion.…”
Section: Resultssupporting
confidence: 84%
“…The C–C distances at the layer boundaries are nearly equal to each other (0.3328 nm for m =1 and 0.3325 nm for m =2) and also comparable to those of the ZrC and Al 4 C 3 crystals, in accord with the principle of the formation of layered carbides in the Zr–Al–C system 2 . The principle could also be applicable to the recently reported layered carbides Zr 4 Al 3 C 6 , Zr 5 Al 6 C 9 , and Zr 7 Al 6 C 11 14 . However, these materials were only recognized under TEM; hence, a precise structural characterization would be needed for further discussion.…”
Section: Resultssupporting
confidence: 84%
“…There are two possible reasons. First, the crystal structures can be described as nonstoichiometric transition metal carbides (MC x ) in the NaCl-type structure being interleaved by Al 3 C 2 units for Zr 2 Al 3 C 4 and Zr 3 Al 3 C 5 , 11,12,25,26 and by close-packed planes of Al for Ti 3 AlC 2 and Ti 2 AlC. 6,7,26 Furthermore, the coupling between TiC x slabs and Al atomic planes in Ti 3 AlC 2 and Ti 2 AlC is conspicuously weaker than that between ZrC x blocks and Al 3 C 2 slabs in Zr 2 Al 3 C 4 .…”
Section: B Composition Of Oxide Scalesmentioning
confidence: 99%
“…49 There exist five independent elastic constants for hexagonal structures, c 11 , c 12 , c 13 , c 33 , c 44 and one dependent constant c 66 = (c 11 Àc 12 )/2. The calculated elastic constants, together with the available experimental and theoretical results from others, 6,34,37,41,42 are listed in Table 3. It can be seen that our calculated values are in good agreement with those from the previous studies.…”
Section: Elastic Propertiesmentioning
confidence: 99%
“…Zr 3 Al 3 C 5 ‐based composites were fabricated by Hashimoto et al in 1998, meanwhile these composites were reported to display satisfactory oxidation resistance. The Zr 4 Al 3 C 6 compound was identified and suggested as a metastable phase by Lin et al in 2007. Then in 2008, Zr 2 Al 4 C 5 and Zr 3 Al 4 C 6 were synthesized and characterized by X‐ray powder diffraction by Sugiura et al .…”
Section: Introductionmentioning
confidence: 99%